Improved cardiac outcomes with combined atenolol and diazepam intervention in seizure - Read, Morgayn I.; Millen, Rebecca N.; McCann, Dominic M.; Harrison, Joanne C.; Kerr, Douglas S.; Sammut, Ivan A. (Epilepsia (Copenhagen), 2018)
Summary Objective Altered autonomic activity has been implicated in the development of cardiac dysfunction during seizures. This study investigates whether intervening in seizure progression with diazepam will reduce seizure‐induced cardiomyopathy. Second, this study examines the hypothesis that combining atenolol with diazepam, as an intervention after seizure onset, will combat cardiac injury during status epilepticus. Methods Male Sprague‐Dawley rats were implanted with electroencephalographic/electrocardiographic electrodes to allow simultaneous recordings during seizures induced by intrahippocampal (2 nmol, 1 μL) kainic acid (KA). Subcutaneous saline, atenolol (5 mg·kg−1), diazepam (5 mg·kg−1), or atenolol and diazepam (n = 12/group) were administered at 60 minutes post‐KA and daily for 7 days, at which point echocardiography, susceptibility to aconitine‐induced arrhythmias, and histology were evaluated. Results Seizure activity was associated with immediately increased heart rate, QTc interval, and blood pressure (BP; 10%‐30% across indices). Seven days postseizure, saline‐treated animals were found to have reduced left ventricular function, increased fibrotic scarring, and an elevated risk of aconitine‐induced arrhythmias. Diazepam treatment significantly reduced cumulative seizure behaviors by 79% compared to saline‐treated animals but offered no cardiac protection. Diazepam significantly raised BP (35%) and increased the risk of bigeminal arrhythmias (36%) compared to saline‐treated animals. Atenolol administration, either alone or with diazepam, reduced heart rate, QTc interval, and BP back to control levels. Atenolol also preserved cardiac morphology and reduced arrhythmia risk. Significance Attenuation of seizure with diazepam offered no cardiac protection; however, coadministration of atenolol with diazepam prevented the development of seizure‐induced cardiac dysfunction. This study demonstrates that atenolol intervention should be strongly considered as an adjunct clinical treatment to reduce cardiomyopathy during seizures.